Deep-sea seven-arm octopus hijacks jellyfish in shallow waters - Rosa, Rui (2020)
Pelagic octopods have secondarily left the seafloor and evolved a holopelagic existence. One of the most striking adaptations among a suite of related pelagic octopod families (superfamily Argonautoidea) is their associations with gelatinous zooplankton (jellyfishes and salps). Here, we report a unique interaction between a male octopod (Haliphron atlanticus) and a jellyfish (Pelagia noctiluca) at the sea surface. The oral-to-oral surface orientation of this encounter and sizes of the animals seem not to fit the explanations of camouflage, shelter, and/or transportation for the octopod or “weapons stealing” strategies observed to date in other pelagic octopods. While maneuvering the jelly, H. atlanticus appears to use the jelly’s marginal nematocystic tentacles for protection. This constitutes further evidence that all four octopod families of the Argonautoidea display various interactions with gelatinous zooplankton.